Effect of Physical Training on the Adipose Tissue of Diet-induced Obesity Mice: Interaction Between Reactive Oxygen Species and Lipolysis - de Farias, J. M.; Bom, K. F.; Tromm, C. B.; Luciano, T. F.; Marques, S. O.; Tuon, T.; Silva, L. A.; Lira, F. S.; de Souza, C. T.; Pinho, R. A. (Hormone and Metabolic Research, 2013)
It is well known that high-fat diets (HFDs) induce obesity and result in an increase in oxidative stress in adipose tissue, which leads to an impairment of fat mobilization by a downregulation of the lipases, such as hormone-sensitive lipase (HSL) and adipose triglyceride lipase (ATGL). On the other hand, exercise training leads to a reduction in adipose tissue and an improvement of antioxidant status and the lipolytic pathway. Our aim was to examine the influence of exercise and moderate intensity training on oxidative stress parameters and the relationship between the proteins involved in the lipolysis of animals subjected to a high-fat fed diet. Twenty-four mice were used and divided into 4 groups (n=6): standard diet (SD); standard diet plus exercise (SD+Ex); high-fat diet (HFD); and high-fat diet plus exercise (HFD+Ex). The animals received HFD for 90 days and submitted to a daily training protocol in swinging. The animals were euthanized 48 h after the last session of exercise. White adipose tissue epididymal fat was excised for the measurement of oxidative stress parameters and protein levels of lipolytic enzymes by Western blotting. The results show an increase in body weight after 90 days of HFD, and exercise training prevented great gain. In adipose tissue, lipid peroxidation and protein carbonylation increased after HFD and decreased significantly after exercise training. The protein level of CGI-58 was reduced, and FAS was increased in the HFD than in SD, whereas ATGL exhibited an increase (p<0.05) in HFD than in SD. The exercise plays a significant role in reducing oxidative damage, along with the regulation of proteins that are involved in the lipolysis of animals exposed to HFD.
Keywords: exercise training; high-fat diet; epididymal fat; oxidative stress; lipolysis